من مـــمـــيّزات الخــــط الـعــربـي في قراءة المصحف: تــــدويـــن وتـــــــطـــويـر وتــــــطـبـيـق - كريم عبد الله مؤمن (Universitas Negeri Malang, 2022)
The calligraphy regards as one of the civilization and culture of the mankind. It influence, plays the roles in correspondence or conversation in a written form. Thus, from a certain period of time to another or from one generation to another. Aside from the renounce it has gained through the the Glorious Quran that is revealed through it. And this is the goal that this paper pursed through the letters that are among the knowledge that Allah taught Adam (A.S). Upon all this, point has negated the unanimous rumor usually said that the ancient Arabs knows nothing about the Arabic syntax , nor rafu’or nasbu and hamzah. At this junction, Ibn Faris said there is no claim that the ancient Arabs had known better in the handwriting and the calligraphy than any other people rather there is no difference between this generation with that of the ancient Arabs .To buttress it, It is believed that none of us knows better about calligraphy, handwriting and reading than one other. And Allah says: “He taught him eloquent speech”. Indeed, how such fluency could be attained, without having knowledge about the Alphabets. While not that, He who taught Adam the whole names is the one who taught him the Arabic alphabets of al-allif, al-baa, a-ljiim, al-ddal. However, it is evident that: the calligraphy is better than the statement ones. This is because the statement teaches the present era only, while the handwriting format mostly teaches the present era and the forthcoming ones. On this note, Azzarnujiy said: Whatever memorized is usually quickly forgotten, compare to that of the written document. Hence, this research seeks to shed lights on the Arabic calligraphy, its meaning, establishment and development. More so, the Glorious Quran calligraphy, its compilation, development and calligraphy review aspect of it.